Mulheres católicas em ação: caridade, saúde e divulgação de ciências em Belo Horizonte (1897-1936) - Polyana Aparecida Valente Vareto (2016)
The main objective of this work was to analyse the agency of lay women in catholic associations, mainly on health and education aid in Belo Horizonte city, between 1897 and 1936. This period was chosen because the establishment of Belo Horizonte represents the modernisation and urbanisation process in the state of Minas Gerais. There was a wide number of assistance groups during this period, from which we highlight the catholic women groups. We believe that catholic female associations were characterized not only by Christian charity, but also by a scientific philanthropy guided by moral and scientific values. Also, we sought to show that those groups granted women access to the public sphere, as well as the creation of an agenda linked to female interests at that time. It was not our objective to carry out a gender analysis. We aimed at producing a work linked to the history of women, in the sense of understanding catholic lay women as social actors that have chosen philanthropy to act beyond the domestic space. We conclude that catholic female associations in Belo Horizonte results from the combination between the mid-19th century catholic reformism and a socio-political project of the elites of Minas Gerais. This socio-political project aimed at protecting and controlling childhood and families, shaping a modern society which was morally good and healthy.